Diseases of poultry (Iowa State University Press, 2008)
The book covers both common and uncommon diseases, and chapters are organized by disease type, including viral, bacterial, fungal, parasitic diseases as well as others, such as nutritional, developmental, metabolic, noninfectious diseases and toxins. Each disease section provides detailed coverage of history, etiology, pathobiology, diagnosis, and intervention strategies, as well as the economic and public health significance of each disease.